2019
DOI: 10.1016/j.cell.2019.09.009
|View full text |Cite|
|
Sign up to set email alerts
|

An Allosteric Anti-tryptase Antibody for the Treatment of Mast Cell-Mediated Severe Asthma

Abstract: Highlights d Increased tryptase levels in asthma that is independent of type 2 inflammation d Higher active allele b-tryptase count associated with lesser omalizumab response d Discovery, biochemistry, and structure of a noncompetitive inhibitory anti-tryptase d Favorable PK and potent inhibition of tryptase activity in mouse and primate models

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 95 publications
0
64
0
Order By: Relevance
“…Balb/c mice are characterized by easy reproduction and minimal weight variation between males and females. While the balb/c mouse serves as a general-purpose animal model, this strain is used extensively for hybridoma and monoclonal antibody production, for example, for the formation of antineuropilin-1 antibodies [7], antibody anti-tryptase [8], and very useful for cancer therapy and immunology study [9]. Aged balb/c mice become susceptible to infection with Streptococcus pyogenes, representing a possible analogy with decreased resistance to infection in elderly humans [10].…”
Section: Discussionmentioning
confidence: 99%
“…Balb/c mice are characterized by easy reproduction and minimal weight variation between males and females. While the balb/c mouse serves as a general-purpose animal model, this strain is used extensively for hybridoma and monoclonal antibody production, for example, for the formation of antineuropilin-1 antibodies [7], antibody anti-tryptase [8], and very useful for cancer therapy and immunology study [9]. Aged balb/c mice become susceptible to infection with Streptococcus pyogenes, representing a possible analogy with decreased resistance to infection in elderly humans [10].…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells contribute to the pathobiology of severe asthma by mediating airflow obstruction and AHR [202]. A role for mast cells in severe asthma was shown with imatinib, which blocks stem cell factor signalling by inhibiting the mast/stem cell growth factor receptor KIT with reductions in airway methacholine reactivity, serum tryptase levels, and airway mast cell counts [203].…”
Section: Mast Cellsmentioning
confidence: 99%
“…A role for mast cells in severe asthma was shown with imatinib, which blocks stem cell factor signalling by inhibiting the mast/stem cell growth factor receptor KIT with reductions in airway methacholine reactivity, serum tryptase levels, and airway mast cell counts [203]. Recent studies identified that mast cell-derived tryptase, the dominant secretory granule protein in mast cells, is elevated in BALF and blood from severe asthmatics with either type 2-low or type 2-high disease [138,202]. Moreover, due to common polymorphisms in the two genes producing b-tryptase, it is possible to have 2,3 or 4 active b-tryptase alleles, and serum tryptase levels correlate with the number of active b-tryptase alleles [202].…”
Section: Mast Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results for protease production and identification of rAbs to MT-SP1 (aka, matriptase), and urokinase plasminogen activator (uPA) showed that conformationally selective inhibitory antibodies can be identified from a naïve human Fab library displayed on bacteriophage. Several inhibitory antibodies have been developed to other proteases including HGFA [10], Factor XIa [11], MMP9 [12] and β-tryptase [13]. Another advantage of rAbs is that the antibody sequence of the binder allows for in vitro affinity maturation, mimicking an immune response, to select Abs with higher affinity and lower off-rate [14].…”
Section: Introductionmentioning
confidence: 99%